(untitled) (TAMADDUN NURI JURNALI, 2024)
In the article, the author provides information about folk ideas after the birth of heroes in epics. In most Karakalpak folk heroic epics, rituals performed after the birth of a child acquire a vital character. That is, more attention is paid to such rituals as circumcision, circumcision, choice of name, wedding, in order to reveal the image of the future hero. This indicates that the roots of the Karakalpak folk epic are associated with ancient times.